2020
DOI: 10.1136/jitc-2020-000940
|View full text |Cite
|
Sign up to set email alerts
|

In situimmunization of a TLR9 agonist virus-like particle enhances anti-PD1 therapy

Abstract: BackgroundCMP-001 is a novel Toll-like receptor-9 agonist that consists of an unmethylated CpG-A motif-rich G10 oligodeoxynucleotide (ODN) encapsulated in virus-like particles. In situ vaccination of CMP-001 is believed to activate local tumor-associated plasmacytoid dendritic cells (pDCs) leading to type I interferon secretion and tumor antigen presentation to T cells and systemic antitumor T cell responses. This study is designed to investigate if CMP-001 would enhance head and neck squamous cell carcinoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…We recently demonstrated that the efficacy of CMP-001 depends on generation of an anti-Qβ antibody response which allows for opsonization of CMP-001, uptake by pDCs and subsequent production of IFN-α. 2 3 We also demonstrated the antitumor activity of CMP-001 in a mouse model is T cell dependent. 4 Nevertheless, much remains to be understood about the mechanism of action of CMP-001, how it alters various immune cells found in the TME and how it is the same or different from soluble TLR9 agonists.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…We recently demonstrated that the efficacy of CMP-001 depends on generation of an anti-Qβ antibody response which allows for opsonization of CMP-001, uptake by pDCs and subsequent production of IFN-α. 2 3 We also demonstrated the antitumor activity of CMP-001 in a mouse model is T cell dependent. 4 Nevertheless, much remains to be understood about the mechanism of action of CMP-001, how it alters various immune cells found in the TME and how it is the same or different from soluble TLR9 agonists.…”
Section: Introductionmentioning
confidence: 70%
“…Intratumoral injection of CMP-001, with the goal of altering the TME and successfully inducing Open access an in situ antitumor immune response, is showing considerable promise in early-phase clinical trials. [1][2][3][4] Encouraging results have also been found with intratumoral injection of soluble TLR9 agonists. 50 Despite this, the long-term feasibility of using soluble TLR9 agonists is limited by its sensitivity to nucleases and short half-life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, CMP‐001 dramatically enhanced tumor response to anti‐PD‐1 therapy and was shown to activate plasmacytoid dendritic cells (pDCs), as well as natural killer (NK) cells in a human papilloma virus‐positive (HPV+) tumor mouse model. [ 159 ] CMP‐001 is currently undergoing clinical trials in combination with PD‐1 blockade in multiple tumor types such as melanoma, colon, HNSCC, and lymphoma.…”
Section: Nanoparticles Are An Advantageous Methods For Delivering Nucleic Acid Vaccinesmentioning
confidence: 99%
“…Combining anti-PD-1 with CMP-001 (a TLR-9 agonist) to treat head and neck squamous cell carcinoma (HNSCC) had a better effect and prolonged the survival time of mouse, compared with anti-PD-1 alone. And CMP-001+anti-PD-1 induced anti-tumor response depends on activation of CD8+ T cells (Cheng et al, 2020). In addition to depending on CD8+ cells, there are other mechanisms that promote the efficacy of checkpoint blockade therapy.…”
Section: Checkpoint Blockade Immunotherapymentioning
confidence: 99%